Correlation between the osteoporosis self-assessment tool for Asians index and QCT-derived bone parameters: a cross-sectional analysis of lumbar spine mineral density and content - Li, Cheng; Lin, Yang; Jiang, Wenyong; Wang, Ye; Chang, Xuehui; Yang, Fan (Frontiers in Surgery, 2026)
ObjectiveTo correlate the Osteoporosis Self-assessment Tool for Asians (OSTA) index with lumbar QCT-measured bone mineral density (BMD) and bone mineral content (BMC), and assess its utility in evaluating lumbar spine BMD/BMC.MethodsFrom Jan 2023 to Jun 2024, 366 patients scheduled for lumbar spine surgery were enrolled. All underwent lumbar CT, QCT, and DXA. Spearman correlation analyzed OSTA vs. QCT-BMD and QCT-BMC. Patients were categorized by DXA T-scores into osteoporotic or non-osteoporotic groups. ROC curves were plotted to determine AUC, optimal cutoff, sensitivity, and specificity.ResultsThe OSTA index showed a moderate, statistically significant correlation with QCT-BMD and QCT-BMC (P < 0.01). Based on DXA diagnosis, QCT-BMC yielded AUCs of 0.712 (men) and 0.745 (women) for osteoporosis, indicating moderate diagnostic value. The optimal cutoffs were 663.86 mg for men and 521.65 mg for women, with sensitivities of 57.6% and 59.5%, respectively.ConclusionAs a screening tool, the OSTA index can help identify high-risk individuals undergoing spinal surgery who are likely to have low lumbar trabecular BMD and BMC as measured by QCT. Diagnostic thresholds for osteoporosis may be set at lumbar QCT-BMC <663.86 mg in men or <521.65 mg in women.